Highlighting clinical needs in Clostridium difficile infection: the views of European healthcare professionals at the front line. Issue 2 (June 2015) - Aguado, J.M.; Anttila, V.J.; Galperine, T.; Goldenberg, S.D.; Gwynn, S.; Jenkins, D.; Norén, T.; Petrosillo, N.; Seifert, H.; Stallmach, A.; Warren, T.; Wenisch, C.; et al.
Summary: Background: Clostridium difficile infection (CDI) is the leading cause of infectious nosocomial diarrhoea in Europe. Despite increased focus, its incidence and severity are increasing in many European countries. Aim: We developed a series of consensus statements to identify unmet clinical needs in the recognition and management of CDI. Methods: A consortium of European experts prepared a series of 29 statements representing their collective views on the diagnosis and management of CDI in Europe. The statements were grouped into the following six broad themes: diagnosis; definitions of severity; treatment failure, recurrence and its consequences; infection prevention and control interventions; education and antimicrobial stewardship; and National CDI clinical guidance and policy. These statements were reviewed using questionnaires by 1047 clinicians involved in managing CDI, who indicated their level of agreement with each statement. Findings: Levels of agreement exceeded the 66% threshold for consensus for 27 out of 29 statements (93.1%), indicating strong support. Variance between countries and specialties was analysed and showed strong alignment with the overall consensus scores. Conclusion: Based on the consensus scores of the respondent group, recommendations are suggested for the further development of CDI services in order to reduce transmission and recurrence and to ensure that appropriate diagnosis and treatment strategies are applied across all healthcare settings.